Morphology‐Controlled Aluminum‐Doped Zinc Oxide Nanofibers for Highly Sensitive NO2 Sensors with Full Recovery at Room Temperature. Issue 9 (23rd July 2018) - Sanger, Amit; Kang, Sung Bum; Jeong, Myeong Hoon; Im, Min Ji; Choi, In Young; Kim, Chan Ul; Lee, Hyungmin; Kwon, Yeong Min; Baik, Jeong Min; Jang, Ho Won; Choi, Kyoung Jin
Abstract: Room‐temperature (RT) gas sensitivity of morphology‐controlled free‐standing hollow aluminum‐doped zinc oxide (AZO) nanofibers for NO2 gas sensors is presented. The free‐standing hollow nanofibers are fabricated using a polyvinylpyrrolidone fiber template electrospun on a copper electrode frame followed by radio‐frequency sputtering of an AZO thin overlayer and heat treatment at 400 °C to burn off the polymer template. The thickness of the AZO layer is controlled by the deposition time. The gas sensor based on the hollow nanofibers demonstrates fully recoverable n‐type RT sensing of low concentrations of NO2 (0.5 ppm). A gas sensor fabricated with Al2 O3 ‐filled AZO nanofibers exhibits no gas sensitivity below 75 °C. The gas sensitivity of a sensor is determined by the density of molecules above the minimum energy for adsorption, collision frequency of gas molecules with the surface, and available adsorption sites. Based on finite‐difference time‐domain simulations, the RT sensitivity of hollow nanofiber sensors is ascribed to the ten times higher collision frequency of NO2 molecules confined inside the fiber compared to the outer surface, as well as twice the surface area of hollow nanofibers compared to the filled ones. This approach might lead to the realization of RT sensitive gas sensors with 1D nanostructures. Abstract : Room‐temperature gas sensitivity of morphology‐controlled free‐standing aluminum‐doped zinc oxide nanofibers for nitrogen dioxide NO2 gas sensors is presented. Based on finite‐difference time‐domain simulations, room‐temperature sensitivity of hollow nanofiber sensors is ascribed to ten times higher collision frequency of NO2 molecules confined inside the fiber compared to the outer surface as well as twice the surface area of hollow nanofibers compared to filled ones.